2002
DOI: 10.1002/joc.661
|View full text |Cite
|
Sign up to set email alerts
|

Possible influence of QBO on teleconnections relating Indian summer monsoon rainfall and sea‐surface temperature anomalies across the equatorial pacific

Abstract: The relationship between the all-India monsoon rainfall and sea-surface temperature (SST) anomalies over different Niño regions of the equatorial Pacific Ocean have been examined from 1949 to 1995 using the full time series, as well as by grouping the seasonal rainfall and SST data according to phases of the Quasi-Biennial Oscillation (QBO) at the 50-hPa level. The results suggest that Indian monsoon rainfall shows the strongest inverse correlation with the SST anomalies over the Niño 3 region for all the seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In the case of El Niño, there are several regions in the tropical Pacific that have been used for analysing the role of El Niño on climate conditions in different parts of the world. Related to the Indian landmass, Chattopadhyay and Bhatla (2002) conducted a detailed analysis of the relationship between summer monsoon rainfall and SST anomalies over the different Niño regions and reported the strongest inverse correlation with the Niño 3 region. Furthermore, majority of the studies examining the relationship between Indian summer monsoon rainfall and ENSO have taken into consideration the Niño 3 index (Krishna Kumar et al , 2006), therefore the use of Niño 3 index in the present study will enable comparison with previous studies.…”
Section: Datasetsmentioning
confidence: 99%
“…In the case of El Niño, there are several regions in the tropical Pacific that have been used for analysing the role of El Niño on climate conditions in different parts of the world. Related to the Indian landmass, Chattopadhyay and Bhatla (2002) conducted a detailed analysis of the relationship between summer monsoon rainfall and SST anomalies over the different Niño regions and reported the strongest inverse correlation with the Niño 3 region. Furthermore, majority of the studies examining the relationship between Indian summer monsoon rainfall and ENSO have taken into consideration the Niño 3 index (Krishna Kumar et al , 2006), therefore the use of Niño 3 index in the present study will enable comparison with previous studies.…”
Section: Datasetsmentioning
confidence: 99%
“…This author proposed a conceptual model for drought or flood years in the Indian monsoon based on the magnitudes and phases of these three factors and argued that the QBO is the primary factor driving the biennial component of ISM interannual variability (Khandekar, 1998). More recently, Chattopadhyay and Bhatla (2002) showed that the QBO may explain the different behavior of the ISM in ENSO years: easterly phases of QBO at 50 hPa during the monsoon season associated to ENSO events are likely to cause droughts, while westerly QBO phases are likely to result in a normal monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…During the same season, strong surface winds generate sea salt aerosols at lower levels (Moorthy, Satheesh, and Murthy 1997;Sivaprasad and Babu 2012). Atmospheric phenomena such the as El Niño Southern Oscillation (ENSO) and Quasi-Biennial Oscillation (QBO) have been observed in the study area (Goswami 1997;Meehl and Arblaster 2001;Chattopadhyay and Bhatla 2002;Sankar, Kumar, and Reason 2011;Shalin and Sanilkumar 2014). Consequently, the influence of such phenomena on the modulation of aerosol concentration can also be expected.…”
Section: Introductionmentioning
confidence: 91%